Chlorogenic Acid-Cucurbit[n]uril Nanocomplex Delivery System: Synthesis and Evaluations for Potential Applications in Osteoporosis Medication - Jiang Y; Qi H; Wang M; Chen K; Chen C; Xie H (International Journal of Nanomedicine)
Yunqing Jiang,1,* Haowen Qi,2,* Mingjuan Wang,1 Kai Chen,3 Chen Chen,1 Haifeng Xie2 1Department of Endodontics, The Affiliated Stomatological Hospital of Nanjing Medical University, State Key Laboratory Cultivation Base of Research, Prevention and Treatment for Oral Diseases, Jiangsu Province Engineering Research Center of Stomatological Translational Medicine, Nanjing, 210029, People’s Republic of China; 2Department of Prosthodontics, The Affiliated Stomatological Hospital of Nanjing Medical University, State Key Laboratory Cultivation Base of Research, Prevention and Treatment for Oral Diseases, Jiangsu Province Engineering Research Center of Stomatological Translational Medicine, Nanjing, 210029, People’s Republic of China; 3Collaborative Innovation Center of Atmospheric Environment and Equipment Technology, Jiangsu Key Laboratory of Atmospheric Environment Monitoring and Pollution Control, School of Environmental Science and Engineering, Nanjing University of Information Science and Technology, Nanjing, 210044, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chen Chen, Department of Endodontics, The Affiliated Stomatological Hospital of Nanjing Medical University, State Key Laboratory Cultivation Base of Research, Prevention and Treatment for Oral Diseases, Jiangsu Province Engineering Research Center of Stomatological Translational Medicine, Nanjing, 210029, People’s Republic of China, Tel +8625 69 593 031, Fax +8625 86 516 414, Email ccchicy@njmu.edu.cn Haifeng Xie Department of Prosthodontics, The Affiliated Stomatological Hospital of Nanjing Medical University, State Key Laboratory Cultivation Base of Research, Prevention and Treatment for Oral Diseases (Nanjing Medical University), Jiangsu Province Engineering Research Center of Stomatological Translational Medicine, Nanjing, 210029, People’s Republic of China, Tel +8625 69 593 081, Fax +8625 86 516 414, Email hfxie@njmu.edu.cn; xhf-1980@126.comPurpose: Based on nanomedicine strategies, this study employed cucurbit[7]uril (Q[7]) as the macromolecular carrier to synthesize nanocomplex drug delivery system for chlorogenic acid (CGA). The nanocomplex drug delivery system is intended to overcome the unsatisfactory biocompatibility and bioavailability of CGA and realizing its potential role in long-term osteoporosis (OP) medication.Methods: The nanocomplex was synthesized by the reflux stirring method. The chemical structure of the nanocomplex was characterized by Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), X-ray diffraction analysis (XRD), UV-visible spectrophotometry (UV-vis), zeta potential analysis and transmission electronic microscope (TEM). The Cell Counting Kit-8 (CCK-8) assay, Live/Dead staining assay, and cytoskeleton staining were conducted to testify the biocompatibility of the nanocomplex. The release assay, Ferric Reducing Ability of Plasma (Frap) assay and Reactive oxygen species (ROS) staining were implemented to evaluate the release profile of CGA as well as its remaining antioxidative levels.Results: CGA and Q[7] formed hydrogen bonding through an exclusion interaction, with the binding ratio more than 1:1. The nanocomplex had a crystalline and spherical-like structure and improved thermal stability. The nanocomplex demonstrated better biocompatibility than free CGA. The release profile of CGA from the nanocomplex was much steadier, and 70% of CGA was released in 5 days. The CGA released from the nanocomplex maintained its antioxidative properties at high levels and effectively eliminated the accumulated ROS in MC3T3-E1 cells under oxidative stress.Conclusion: Q[7] has been demonstrated to be an ideal nanocarrier for CGA and the nanocomplex delivery system holds the potential for the long-term medication strategy of OP. Keywords: Osteoporosis medication, Chlorogenic acid, Cucurbit[n]uril, Nano drug delivery system, Chemical analysis